MODEL TRANSFORMASI DIGITAL PENDIDIKAN ISLAM: ANALISIS INTEGRASI TEKNOLOGI PEMBELAJARAN DI MADRASAH - M. Agus Kurniawan; Dedi Lazwardi; Sucipto (CV JK Riset Publishing Group, 2026)
Digital transformation in Islamic education at madrasah represents both a strategic challenge and opportunity in the Industrial Revolution 4.0 era. This study aims to analyze the learning technology integration model in madrasah and identify factors influencing its effectiveness. The research employed a mixed methods approach with quantitative surveys involving 120 madrasah teachers and in-depth interviews with 15 key informants across five Indonesian provinces. Results indicate that 67.5% of madrasah have partially integrated learning technology, yet only 23.3% successfully implemented it comprehensively. Primary inhibiting factors include limited digital infrastructure, inadequate teacher competencies, and insufficient institutional policy support. The conclusion suggests that digital transformation in Islamic education requires a holistic model that synergistically integrates technical, pedagogical, and Islamic values aspects.